PENGARUH MANFAAT YANG DIRASAKAN WAJIB PAJAK, KEPERCAYAAN TERHADAP APARAT PAJAK, SOSIALISASI PAJAK, DAN PENGHASILAN WAJIB PAJAK TERHADAP KEPEMILIKAN NOMOR POKOK WAJIB PAJAK (NPWP) (Studi Empiris Pada Pengusaha UMKM di Kota Pekanbaru) - Khairah Ummami; Zirman Zirman; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect caused by the variable benefits received by taxpayer, trust in tax authorities, tax socialization, and taxpayer’s income with OwnershipTaxpayer Identification Number (TIN). This study uses purposive sampling with 100 samples obtained from the calculation formula slovin. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 20 for Windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on the variable taxpayer identification number (TIN). Partial regression test (t test) indicates that the variable benefits received by taxpayer, trust in tax authorities, tax socialization partially effect the variable ownership taxpayer identification number (TIN). The result of the study also showed that taxpayer’s income does not effect the variable ownership taxpayer identification number (TIN). The magnitude of the effect caused by Adjusted R2 by four variables together against the dependent variable 32.6%, while the remaining 67.4% is influenced by other variables not examined in this study.Keywords: Taxpayer, Trust , Socialization, Income.